2021
DOI: 10.21203/rs.3.rs-147767/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Food and Nutrition Literacy Status and Its Correlates in Iranian Senior High-School Students

Abstract: Background: Planning food and nutrition literacy (FNL) promoting interventions require a better understanding of the FNL status of the target group and its correlates. Aims: This study aimed to examine the FNL status and its determinants in Iranian senior high-school students. Methods: In this cross-sectional study, socioeconomic, demographic, anthropometric measures, as well as academic performance of 626 senior high-school students were assessed. Besides, FNL and its six components (food and nutrition knowle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Poor dietary habits are implicated in ∼20% of deaths worldwide world each year (3). As a crucial influencing factor of eating behavior, nutrition literacy affected people's diet choice and health (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Poor dietary habits are implicated in ∼20% of deaths worldwide world each year (3). As a crucial influencing factor of eating behavior, nutrition literacy affected people's diet choice and health (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…However, in our study, students obtained the lowest score in the skill application dimension of nutrition literacy [31]. This result may be due to the ease of access to a large volume of health and nutrition-related content today, causing students to become confused when selecting accurate and precise information and how to apply it effectively [7,30] The study results showed that the mean overall score of students' eating behavior was 3.18 out of 5. This result was consistent with Lee C-K et al, and Liday DM et al studies [18,32], but did not match Liao and colleagues' findings.…”
Section: Discussionmentioning
confidence: 69%
“…Additionally, 80% of participants in this study were found to have poor nutrition literacy [30]. In Ashoori et al, on Iranian youth who used our original questionnaire form, the average score for nutritional literacy was obtained as 52.1 out of 100, indicating low levels of nutritional literacy among Iranian youth and highlighting the need to improve their nutritional literacy skills [7]. The difference in nutrition literacy levels may be due to limited exposure to nutrition information among certain population groups, differences in individuals' education levels, societal pressures and norms, or socio-economic status.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Past research has focused on factors affecting food literacy, nutrition literacy, or food and nutrition literacy or the impact of these literacy levels on food intake and diet quality; or the relationship between nutrition education and sustainable and healthy eating behaviours. [12][13][14][15][16][17][18][19] To our knowledge, this is the first study to investigate the relationship between level of nutrition knowledge and sustainable food literacy. The results of this study indicated that participants with low nutrition knowledge had lower sustainable food knowledge scores than those in the medium and high nutrition knowledge groups.…”
Section: Discussionmentioning
confidence: 99%